EFFECT OF AUDITOR'S EXPERIENCE AND ETHICS ON AUDIT QUALITY IN PUBLIC ACCOUNTANT OFFICES IN BANDUNG CITY - Muhammad Rizal Satria (Universitas Pasundan, 2020)
The purpose of this research was to know the effect of the Auditor Experience and the Auditor Ethics toward Audit Quality. The study was conducted using a survey method towards forty-five auditor who worked on thirteen public accountant firm in the city of Bandung. Data analysis was performed by multiple linear regression models. Hypothesis testing was done to determine whether there is any influence on the Auditor Experience and the Auditor Ethics towards the Audit Quality either simultaneously or partially. The test result indicates that simultaneously, the Auditor Experience and the Auditor Ethics are significantly affecting the Audit Quality. The test result also indicates that partially, either the Auditor Experience or the Auditor Ethics are significantly affecting the Audit Quality.